SAT0199 PARTICULARITIES OF SJÖGREN SYNDROME IN ELDERLY PATIENTS. (2nd June 2020) - Naceur, I.; Abida, R.; Ben Salem, T.; Said, F.; Khanfir, M.; Ben Ghorbel, I.; Lamloum, M.; Houman, M. H.
Abstract : Background: Sjögren syndrome (SS) is a systemic autoimmune disease mainly described in females at a peak incidence age of 50. It was suggested that elderly onset of disease has particular clinical and biological phenotype. Objectives: The aim of our study is to determine the particularities of SS in elderly patients. Methods: Data of 332 patient fulfilling the American European Consensus Group criteria for Sjögren's syndrome over a period time of 18 years were studied. Clinical and biological features of elderly patients (G1) were described and compared to those of patients aged below 65 years old (G2) using the X2 and Fisher test. Results: A total of 35 elderly were retained: 33 females and 2 males. The mean age of disease onset was 68.8 ± 4.4 years. The average delay (from first sign of the disease to diagnosis) was 1.27 years. The mean age at diagnosis was 70.3 ± 4.7 years. Xerostomia was described by 33 patients (94.3%). Focus score in the minor labial salivary glands pathology was ≥ 1 in 32 patients (91.4%). Two patients had abnormalities in parotid scintigraphy. Xeropthalmia was described by 32 elderly patients (91.4%). Schirmer test was abnormal in 20 cases (57.1%) and Break Up Time test was altered in 20 cases (57.1%). Arthralgia was the most frequent extra-glandular manifestation reported in 74.3% of patients. Fatigue was noted in 12 patients. The other systemic manifestations were: interstitial lung disease (n=13), peripheral neuropathy (n=7), central nervous system involvement (n=5), Raynaud's phenomenon (n=4), myositis (n=2) and renal tubulopathy (n=2). Laboratory findings showed hyperglobulinemia (n=19) and lymphopenia (n=15). Antinuclear antibodies were positive in 25 patients (71.4%) with positive anti-SSA antibodies (n=14) and positive anti-SSB antibodies (n=7). SS was primary in 25 patients. Ten patients had one or more associated autoimmune diseases: cryoglobulinemia (n=4), systemic scleroderma (n=3), systemic lupus erythematosus (n=2), rheumatoid arthritis (n=2) and autoimmune hepatopathy (n=2). Systemic treatments involved corticosteroids for 15 patients, antimalarial agents for 12 patients, nonsteroidal anti-inflammatory drugs for three patients and immunosuppressant agents for nine patients. One patient developed lymphoma. Comparative analysis showed that SS diagnosis was made earlier in elderly with an average delay of 1.27 years in G1 vs 3 years in G2 (p=0.02). Fatigue was more frequent in elderly (63.2% vs 23.8%) p<0.01. Positivity of anti-SSA was also more frequent in elderly (64.9% vs 46.7%; p=0.04). Anti-malarial agents were less prescribed in elderly (36.4% vs 55.3%; p=0.03). There was no significant differences between the two groups concerning the other clinical features, laboratory findings, treatment and outcomes. Conclusion: Regardless of the statistical findings in our study and in the literature, treatment and follow-up of elderly patients with SS must obey to closer attention considering their vulnerability and the complexity of their management. Disclosure of Interests: None declared